War Supplies from Forests of Pilibhit - Chaturvedi, M. D. (Indian Forester, 1942)
The supply of about a hundred thousand cubic feet of scantlings, three lakhs of sal poles, 40 thousand sleepers and timber for stretchers, tool handles and other needs of the Army, represents the contribution of the Pilibhit Forests in 1940-41 towards India's Defence. The extraction and transport of such vast quantities of timber presented problems as interestmg as their solution was ingenious.